قوادري راناأ. د عبدلي فاتح - (:unkn) unknown (My University, 2024)
Abstract The study aims to know the relationship between emotional intelligence and psychological health among physical and sports education teachers, which was based on the descriptive method in its correlative and comparative styles, the sample included 2,000 teachers throughout the country's territory. by using the emotional intelligence scale of Ben Khalifa Fatima and building a psychological health scale after confirming its psychometric properties, the data was also processed through the SPSS 26 Social Science Statistical Programs Package, where the results indicated:  There is a relationship between emotional intelligence and psychological health among physical and sports education teachers.  There is no relationship between emotional intelligence and physical well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and emotional well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and psychological well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and the self-well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and social well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and humanity well-being among physical and sports education teachers.  There are statistically significant differences in the level of emotional intelligence among physical and sports education teachers attributable to professional seniority.  There are statistically significant differences in the level of psychological health among physical and sports education teachers attributable to professional seniority. --------------- Abstract The study aims to know the relationship between emotional intelligence and psychological health among physical and sports education teachers, which was based on the descriptive method in its correlative and comparative styles, the sample included 2,000 teachers throughout the country's territory. by using the emotional intelligence scale of Ben Khalifa Fatima and building a psychological health scale after confirming its psychometric properties, the data was also processed through the SPSS 26 Social Science Statistical Programs Package, where the results indicated:  There is a relationship between emotional intelligence and psychological health among physical and sports education teachers.  There is no relationship between emotional intelligence and physical well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and emotional well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and psychological well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and the self-well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and social well-being among physical and sports education teachers.  There is a relationship between emotional intelligence and humanity well-being among physical and sports education teachers.  There are statistically significant differences in the level of emotional intelligence among physical and sports education teachers attributable to professional seniority.  There are statistically significant differences in the level of psychological health among physical and sports education teachers attributable to professional seniority. -------- L'étude vise à connaître la relation entre l'intelligence émotionnelle et la santé psychologique parmi les enseignants d'éducation physique et sportive, qui s'est basée sur la méthode descriptive dans ses styles corrélatif et comparatif, l'échantillon comprenait 2.000 enseignants sur tout le territoire du pays. en utilisant l'échelle d'intelligence émotionnelle de Ben Khalifa Fatima et en construisant une échelle de santé psychologique après avoir confirmé ses propriétés psychométriques, les données ont également été traitées via le SPSS 26 Social Science Statistical Programs Package, où les résultats ont indiqué :  Il existe une relation entre l'intelligence émotionnelle et la santé psychologique chez les enseignants d'éducation physique et sportive.  Il n'existe aucune relation entre l'intelligence émotionnelle et le bien-être physique chez les enseignants d'éducation physique et sportive.  Il existe une relation entre l'intelligence émotionnelle et le bien-être émotionnel chez les enseignants d'éducation physique et sportive.  Il existe une relation entre l'intelligence émotionnelle et le bien-être psychologique chez les enseignants d'éducation physique et sportive.  Il existe une relation entre l'intelligence émotionnelle et le bien-être de soi chez les enseignants d'éducation physique et sportive.  Il existe une relation entre l'intelligence émotionnelle et le bien-être social chez les enseignants d'éducation physique et sportive.  Il existe une relation entre l'intelligence émotionnelle et le bien-être humain chez les enseignants d'éducation physique et sportive.  Il existe des différences statistiquement significatives dans le niveau d'intelligence émotionnelle parmi les enseignants d'éducation physique et sportive attribuables à l'ancienneté professionnelle.  Il existe des différences statistiquement significatives dans le niveau de santé psychologique des enseignants d'éducation physique et sportive attribuables à l'ancienneté professionnelle. -------------- الملخص هدفت الدراسة إلى معرفة العلاقة بين الذكاء الوجداني والصحة النفسية لدى أساتذة التربية البدنية والرياضية في الطور الثانوي، واعتمدت الدراسة على المنهج الوصفي بأسلوبيه الارتباطي والمقارن، حيث شملت العينة على 2000 أستاذ تربية بدنية ورياضية موزعون على كامل التراب الوطني الجزائري، وتم استخدام مقياس الذكاء الوجداني لبن خليفة فاطمة (2017)، وبناء مقياس خاص بالصحة النفسية لأساتذة التربية البدنية والرياضية، بعد التأكد من خصائصهما السيكومترية، وعولجت البيانات ببرنامج الحزمة الإحصائية للعلوم الاجتماعية SPSSالإصدار 26، حيث أشارت النتائج إلى:  توجد علاقة بين الذكاء الوجداني والصحة النفسية لدى أساتذة التربية البدنية والرياضية.  لا توجد علاقة بين الذكاء الوجداني وبعد الرفاه الجسمي لدى أساتذة التربية البدنية والرياضية.  توجد علاقة بين الذكاء الوجداني وبعد الرفاه الانفعالي لدى أساتذة التربية البدنية والرياضية.  توجد علاقة بين الذكاء الوجداني وبعد الرفاه النفسي لدى أساتذة التربية البدنية والرياضية.  توجد علاقة بين الذكاء الوجداني وبعد الرفاه الذاتي لدى أساتذة التربية البدنية والرياضية.  توجد علاقة بين الذكاء الوجداني وبعد الرفاه الاجتماعي لدى أساتذة التربية البدنية والرياضية.  توجد علاقة بين الذكاء الوجداني وبعد الرفاه الإنساني لدى أساتذة التربية البدنية والرياضية.  توجد فروق ذات دلالة إحصائية في مستوى الذكاء الوجداني لدى أساتذة التربية البدنية والرياضية تعزى للأقدمية المهنية.  توجد فروق ذات دلالة إحصائية في مستوى الصحة النفسية لدى أساتذة التربية البدنية والرياضية تعزى للأقدمية المهنية.
علاقة الصحة النفسية بالذكاء الوجداني وفق متغير الأقدمية المهنية لدى أساتذة التربية البدنية والرياضية في الطور الثانوي "دراسة ميدانية على كل ولايات التراب الوطني الجزائري"